2014
DOI: 10.1007/s13337-014-0192-1
|View full text |Cite
|
Sign up to set email alerts
|

The fecal virome of domesticated animals

Abstract: Next-generation sequencing is a new research tool in our hands helping us to explore still unknown fields of human and veterinary virology. Metagenomic analysis has enabled the discovery of putative novel pathogens and the identification of the etiologic agents of several diseases, solving long-standing mysteries caused by divergent viruses. This approach has been used in several studies investigating fecal samples of livestock, and companion animal species, providing information on the diversity of animal fec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Culture-independent metagenomic approaches can aid in understanding the ecological role, phylogeny, and functionality of gut microbial communities in relation to host physiology 1 – 4 . Metagenomic shotgun sequencing investigations have been used to reveal specific features of the resistome 5 9 , mobilome 10 , 11 , virulome 12 and virome 13 . The increasing prevalence of antimicrobial resistance (AMR) in bacteria is one of the most important challenges facing public health.…”
Section: Introductionmentioning
confidence: 99%
“…Culture-independent metagenomic approaches can aid in understanding the ecological role, phylogeny, and functionality of gut microbial communities in relation to host physiology 1 – 4 . Metagenomic shotgun sequencing investigations have been used to reveal specific features of the resistome 5 9 , mobilome 10 , 11 , virulome 12 and virome 13 . The increasing prevalence of antimicrobial resistance (AMR) in bacteria is one of the most important challenges facing public health.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were subjected to random primed PCR and semiconductor sequencing using the Ion Torrent PGM platform. Library preparation, size selection of library DNA, emulsion PCR, templated Ion Sphere bead enrichment and sequencing, bioinformatics analysis was carried out as described in detail elsewhere (Mihalov-Kovács et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Other study reported in diarrheic dogs, the presence of canine parvovirus 2 (CPV2), canine enteric coronavirus (CcoV), rotavirus, insect and plant viruses, canine kobuviruses and sapoviruses (canine sapovirus 1 and 2). Finally, studies from bird feces (turkey and chicken with enteric disease) showed kobuviruses, calicivirus (Sapovirus and Lagovirus), avianastrovirus and avian reovirus [17].…”
Section: Metagenomics For Viral Diagnostics?mentioning
confidence: 99%
“…Percentage of sequences related to the main categories of existing viruses: vertebrate (blue), plant/fungal (green), invertebrate (brown), protozoan (yellow) viruses and bacteriophages (gray), and unassigned viral sequences (no data available concerning the taxonomic family, indicated in red). The total number of viral contigs is indicated below each pie chart (figure and legend were taken with permission from[17]). http://journals.plos.org/plosone/article?id=10.1371/journal.pone.0087194.…”
mentioning
confidence: 99%